KEPENTINGAN PROGRAM BANDAR SELAMAT SEBAGAI ASAS KESELAMATAN INDUSTRI PELANCONGAN DI BANDARAYA JOHOR BAHRU (Sains Humanika, 2009)
Lately, safety elements and crime are considered as significant issues among visitors especially in urban tourism. Based on these issues, Malaysia has taken the initiative to address this situation by establishing various strategies and among them is the introduction of the Safe City Programme. Johor Bahru City through Johor Bahru City Council as a local authority has implemented the Safe City Programme since 22nd November 2004, where the goal is to enhance the safety quality not only for the local community but also for tourists visiting Johor Bahru. In this study, Singaporean tourists were selected as the main respondents because they are the highest proportion of tourists visiting Johor Bahru. The findings of this study indicates that majority of respondents perceived that all the crime prevention measures taken in the Safe City Programme are important in ensuring the safety of tourists while they are in Johor Bahru. It is hope that from this study, the related parties involved will continuously improve the Safe City Programme and increase the safety level for tourists to the extent that the Johor Bahru City will be considered as a very safe destination to visit.
Keywords: Safety; urban tourism; Safe City Programme